PENINGKATAN KEMAMPUAN CRITICAL THINKING SISWA MELALUI ONLINE LEARNING MANAGEMENT SYSTEM DI SMP SRIWEDARI MALANG - Elita Mega Selvia Wijaya; Rudy Setiawan; Muhammad Rifa’i (LPPM Universitas Islam Darul 'Ulum Lamongan, 2023)
This research is a community service that aims to improve students' critical thinking skills through the implementation of an Online Learning Management System at SMP Sriwedari Malang. The method used in this service is the development and implementation of an Online Learning Management System tailored to the needs of students and the school curriculum. In addition, training and mentoring activities are also carried out for teachers and students to ensure the effectiveness of using the system. Data collection is carried out through observation, interviews, and assessment of student learning outcomes. The results of the service showed that the implementation of the Online Learning Management System succeeded in significantly improving students' critical thinking skills. Students are able to develop better analysis, evaluation, and problem-solving skills through structured and interactive learning in an online system. The use of this system also facilitates collaboration and communication between teachers and students, and provides greater accessibility to learning materials.